Políticas culturais e políticas de identidade em Alagoas: governo Ronaldo Lessa (1999-2006) e governo Teotônio Vilela (2007-2014) - Magalhães, Luíz Fernando Barbosa Gomes (2017)
This study investigates the cultural policies of identity that were conducted by the culture public agencies of the State of Alagoas in two administrations: the Ronaldo Lessa Government (1999-2006) and the Teotônio Vilela Filho Government (2007-2014). It addresses the issue of identity in its inseparable relationship with the "cultural" and narratives of formation and orientation of the nation-state in Brazil - connections that mostly orbit in the sphere of cultural policies and which have been elaborated through a long Intergenerational process, full of conceptual displacements and political struggles. In this sense, it exposes the main moments in which, in the course of the 20th century, and at the beginning of the 21st century, the production of identity politics came together with the elaboration of cultural policies and materialized at the state level, highlighting their essential characteristics, agents and Movements responsible for their texture and the conditions of possibility that allowed their respective articulations. The Alagoan developments of this process were gathered from documentary research and interviews with state agents who participated actively in the elaboration of cultural policies in the mentioned period. From this juncture, the text presents the first policies of valorization of the identity that were conducted in the Lessa Government, its folkloristic outlines and the alienation of the cultural sector in the face of the large identity politics of valorization of the afroalagoanidade that were conducted by other state sectors. Similarly, the text outlines the institutional transformations and adaptation efforts conducted by SECULT to conform to the molds proposed by the Ministry of Culture in its most active period - a process that leads to a restricted assimilation of the UNESCO discourse repertoire, Professionalism in the sector, but that converts the Secretariat into a kind of local executor satellite of the cultural policies prescribed by the MinC.